SME finance in Asia: Recent innovations in fintech credit, trade finance, and beyond - Giulio Cornelli; Vukile Davidson; Jon Frost; Leonardo Gambacorta; Kyoko Oishi (Asian Development Bank Institute (ADBI), 2019)
This study gives an overview of recent innovations in the financing of small and medium-sized enterprises (SMEs) in Asia. While SMEs are an important contributor to employment and gross domestic product in Asia, they often face significant credit constraints. Recently, in the context of Asia's rapidly digitalizing economy, both incumbents and new entrants are developing innovative means of providing SME finance. This includes the growth of fintech credit, big tech providers, and new initiatives in trade finance.
Keywords: G21; G23; G32; F65; F37; O16; 330; small and medium-sized enterprises; fintech; trade finance